PUBLIC SPEAKING LEARNING ASSISTANCE TO INCREASE STUDENTS' CONFIDENCE - Tarigan, Fatin Nadifa; Nasution, Alwi Fahruzy; Hasibuan, Siti Aminah; Nurmayana, Nurmayana; Siregar, Epi Supriyani (Universitas Negeri Medan, 2024)
Public speaking is a skill that everyone, including students, should have to increase their self-confidence. Public speaking cannot be avoided since basically humans often have to do it with various purposes. However, many students feel unable to speak in public because they lack confidence, don't master the material, or don't understand how to do it. This community service activity aims to do learning assistance for public speaking to increase the self-confidence of students at Gajah Mada Middle School, Medan. The methods used were direct lecturer, simulations and interactive discussions regarding the basics of public speaking, effective and good communication techniques, and various tips for developing yourself, especially in terms of public speaking. During the learning assistance, participants received basic material and public speaking techniques as well as direct practice. Meanwhile, the research used qualitative method for collecting data. As for the research results, the community service recommends the following: 1) Add extra hours to improve students™ English speaking, 2) Add contest that can motivate students to increase their confidence in public speaking, especially in English language.